The Concept of Good Governance in The History of Khalifa Umar bin Al-Khattab Leadership - Nasution, Saipul; Ibrahim, Ibnor Azli bin Ibrahim; Rahman, Mariam binti Haji Abdul (Universitas Darussalam Gontor, 2023)
**English**A good governance system is not a term that has emerged recently since, in fact, the system has been exemplified by the Prophet SAW himself. This governance system began when the Prophet SAW formed the Medina Charter. Moreover, the administration and management in Medina are based on Islamic law and a democratic state management model. Following the example of the management of the Prophet SAW, Khalifa Umar bin Khattab implemented a system of governance that balanced the interests of religion and the people. Therefore, it is important to examine this discussion as a guideline for the existing system of governance in Muslim countries today. This was a qualitative study that used written analysis as a method of analyzing data. The main data were obtained through literature sources. The results of the analysis found that the concept of good governance of Khalifa Umar bin al-Khattab was able to guarantee the state during his leadership. The system initiated by Khalifa Umar can actually provide an overview and guidelines for the current system of state governance. **Indonesia**Sistem pemerintahan yang baik bukanlah istilah yang muncul akhir-akhir ini, karena sebenarnya sistem tersebut sudah dicontohkan oleh Nabi SAW sejak dahulu kala. Pengelolaan negeri ini dimulai sejak Nabi SAW membentuk Piagam Madinah. Apalagi penyelenggaraan dan pengelolaan di Madinah didasarkan pada syariat Islam dan model penyelenggaraan negara yang demokratis. Meneladani kepemimpinan Nabi SAW, Khalifah Umar bin Khattab menerapkan sistem pemerintahan yang menyeimbangkan kepentingan agama dan umat. Oleh karena itu, pembahasan ini penting untuk dikaji sebagai pedoman keberadaan sistem pemerintahan yang ada di negara-negara Islam saat ini. Penelitian ini bersifat kualitatif karena menggunakan analisis tertulis sebagai metode analisis data yang diperoleh melalui sumber kepustakaan. Hasil analisis menemukan bahwa konsep good governance pada sejarah kepemimpinan Khalifah Umar bin al-Khattab mampu menjamin negara pada masa kepemimpinannya. Sistem yang digagas Khalifa Umar ini sebenarnya dapat memberikan gambaran dan pedoman bagi sistem ketatanegaraan yang ada saat ini.